Blood Pressure and Heart Rate Alterations through Music in Patients Undergoing Cataract Surgery in Greece. (January 2015) - Merakou, Kyriakoula; Varouxi, Georgia; Barbouni, Anastasia; Antoniadou, Eleni; Karageorgos, Georgios; Theodoridis, Dimitrios; Koutsouri, Aristea; Kourea-Kremastinou, Jenny
Introduction: Music has been proposed as a safe, inexpensive, nonpharmacological antistress intervention. The purpose of this study was to determine whether patients undergoing cataract surgery while listening to meditation music experience lower levels of blood pressure and heart rate. Methods: Two hundred individuals undergoing cataract surgery participated in the study. Hundred individuals listened to meditation music, through headphones, before and during the operation (intervention group) and 100 individuals received standard care (control group). Patients stress coping skills were measured by the Sense of Coherence Scale (SOC Scale). Systolic and diastolic blood pressure and heart rate were defined as outcome measures. Results: According to the SOC Scale, both groups had similar stress coping skills (mean score: 127.6 for the intervention group and 127.3 for the control group). Before entering the operating room (OR) as well as during surgery the rise in systolic and diastolic pressures was significantly lower in the intervention group ( P < 0.001). Among patients receiving antihypertensive therapy, those in the intervention group presented a lower increase only in systolic pressure ( P < 0.001) at both time recordings. For those patients in the intervention group who did not receive antihypertensive treatment, lower systolic blood pressure at both time recordings was recorded ( P < 0.001) while lower diastolic pressure was observed only during entry to the OR ( P = 0.021). Heart rate was not altered between the two groups in any of the recordings. Conclusions: Meditation music influenced patients' preoperative stress with regard to systolic blood pressure. This kind of music can be used as an alternative or complementary method for blood pressure stabilizing in patients undergoing cataract surgery.